2020
DOI: 10.21203/rs.3.rs-60029/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adolescent Sexual and Reproductive Health Care Service Availability and delivery in Public Health Facilities of Plateau State Nigeria

Abstract: To assessed the availability, accessibility, appropriateness and quality of ASRH services in Primary health care facilities in Plateau State, Nigeria, a cross sectional study was conducted in 230 PHCs across the three senatorial zones of Plateau state. Primary data was obtained through face to face interview with heads of facilities from December 2018 to May 2019 using an adapted questionnaire from WHO with five domains ascertaining the extent that ASHR services were available and provided. The questionnaires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(27 reference statements)
0
3
0
1
Order By: Relevance
“…It is crucial to ensure that public health facilities offer reproductive health care services to guarantee their access, to high quality care (Envuladu et al, 2020).…”
Section: Performance Of Health Facilitiesmentioning
confidence: 99%
“…It is crucial to ensure that public health facilities offer reproductive health care services to guarantee their access, to high quality care (Envuladu et al, 2020).…”
Section: Performance Of Health Facilitiesmentioning
confidence: 99%
“…Kurangnya privasi adalah salah satu alasan pemanfaatan layanan kesehatan reproduksi dan seksual remaja yang buruk (13,29). Hal ini dapat menyebabkan kurangnya kepercayaan remaja pada penyedia pelayanan kesehatan yang mengakibatkan remaja memutuskan untuk tidak mengakses pelayanan kesehatan.…”
Section: Kurangnya Privasi Dan Kerahasiaanunclassified
“…To ensure access to SRHS and improve adolescent SRH health seeking, adolescent health services were integrated into the primary healthcare (PHC) centres, which are found in all communities, and are often closer to where adolescents spend the majority of their time [9,15]. We assessed the availability and accessibility of adolescent sexual and reproductive health services (ASRHS) in PHCs in Plateau State [21,22,23], and found that the range of services included in the Nigerian policy were not available in most of the facilities surveyed, and that facilities that did provide SRHS were mainly adult focused (e.g., maternal healthcare) and not adolescent-centred [21,22]. Moreover, we showed that adolescents did not seek SRH care in health facilities and were unwilling to utilize the health facilities for SRH care -even when they were in need [21,23].…”
Section: Introductionmentioning
confidence: 99%